Limiting Availability of Binding Sites for Dehydrogenases on the Cell Membrane of Escherichia coli - Kung, Hsiang-Fu (1972)
Experiments are reported that demonstrate that in E. coli the pyridine nucleotide-independent D- and L-lactate dehydrogenases and the aerobic L-α-glycerophosphate dehydrogenase are membrane bound. These enzymes differed from succinate dehydrogenase in that they could be solubilized by treatment with nonionic detergent while succinate dehydrogenase could not. The binding of these enzymes to membrane was measured in mutants constitutive for the synthesis of various dehydrogenases: in cells in which the amount of dehydrogenases synthesized was greater than in others, the enzymes described above (except succinate dehydrogenase) were found in part in the soluble fraction of the cell extracts. Experiments of oxygen uptake indicate that when a fraction of the enzymes became soluble, this soluble fraction is no longer functional in respiration. These results indicate that it is possible to prevent membrane attachment of certain dehydrogenases by the excess production of other dehydrogenases; it may be that dehydrogenases compete for identical binding sites.